Phylogenetic analysis of Ukrainian seed-transmitted isolate of Soybean mosaic virus - Mishchenko, L.T.; Dunich, A.A.; Shcherbatenko, I.S. (Вiopolymers and Cell, 2018)
Soybean mosaic virus (SMV) is seed transmitted and can cause significant reductions in the yield and seed quality in soybean (Glycine max). The seed transmission rate of different SMV isolates is 0–43 %. The question regarding SMV genes involved in the seed transmission of its isolates remains open. The phylogenetic studies of Ukrainian seed-transmitted SMV isolates have not been conducted. Aim. Phylogenetic analysis of the CP gene region of the SMV isolate, which has the ability to seed transmission. Methods. RNA extraction from plant material, RT-PCR, sequencing, phylogenetic analysis. Results. For the first time, the phylogenetic analysis of 430 nt CP gene sequence of seed-transmitted SMV isolate SKS-18 was performed. The highest level of the nucleotide sequences identity (98.8 %) and amino acid sequences (98.6 %), the isolate SKS-18 has with the Iranian isolates Ar33, Lo3, American isolate VA2, and Ukrainian isolate UA1Gr. Two unique amino acid substitutions (Ser→Cys at position 1 and Lys→Ala at position 2) in the studied CP gene region of SKS-18 are revealed. Conclusions. The isolate SKS-18 is localized in the same cluster with the isolates of the highest nucleotide identity, that may be due to their similar variability. Unique amino acid substitutions in the studied CP gene region of SKS-18 can be involved to its seed transmission and other important functions of the infectious cycle, the identification of which is necessary for the development of effective plant protection measures against viral diseases. Вірус мозаїки сої (ВМС) передається насінням і може спричиняти значні зниження врожаїв та якості насіння рослин сої (Glycine max). Ступінь насіннєвої передачі різних ізолятів ВМС складає 0–43 %. Питання про те, які саме гени ВМС задіяні у процесі насіннєвої передачі його ізолятів досі залишається відкритим. Філогенетичних досліджень для українських ізолятів ВМС, які передаються насінням, не проводилось. Мета. Провести філогенетичний аналіз гена CP ізоляту ВМС, який передається насінням. Методи. Виділення тотальної РНК із рослинного матеріалу, RT-PCR, сиквенування, філогенетичний аналіз. Результати. Вперше проведено філогенетичний аналіз послідовностей ділянки (430 пн) гена капсидного білка ВМС ізоляту SKS-18, який передається насінням. Найвищий відсоток ідентичності за нуклеотидною (98,8 %) та за амінокислотною (98,6 %) послідовністю ізолят SKS-18 має з іранськими ізолятами Ar33, Lo3, американським ізолятом VA2, а також українським ізолятом UA1Gr. У досліджуваній ділянці гену CP ізоляту SKS-18 виявлено унікальні амінокислотні заміщення у позиціях 1 (Ser→Cys) та 2 (Lys→Ala). Висновки. Ізолят SKS-18 локалізується в одному кластері з ізолятами з найбільшою ідентичністю нуклеотидів, що може бути наслідком їх подібної мінливості. Унікальні амінокислотні заміщення у досліджуваній ділянці гену CP ізоляту SKS-18 можуть бути залучені до насіннєвої передачі вірусу та інших важливих функцій інфекційного циклу, з’ясування яких необхідне для розроблення ефективних засобів захисту рослин від вірусних хвороб. Вирус мозаики сои (ВМС) передается семенами и может вызывать значительные снижения урожая и качества семян растений сои (Glycine max). Степень семенной передачи различных изолятов ВМС составляет 0–43 %. Вопрос о том, какие именно гены ВМС задействованы в процессе семенной передачи его изолятов, до сих пор остается открытым. Филогенетических исследований для украинских изолятов ВМС, передающихся семенами, не проводилось. Цель. Провести филогенетический анализ гена CP изолята ВМС, который передается семенами. Методы. Выделение тотальной РНК из растительного материала, RT-PCR, сиквенирование, филогенетический анализ. Результаты. Впервые проведен филогенетический анализ последовательностей участка (430 пн) гена капсидного белка изолята ВМС SKS-18, который передается семенами. Наиболее высокий процент идентичности по нуклеотидной (98,8 %) и аминокислотной (98,6 %) последовательности изолят SKS-18 имеет с иранскими изолятами Ar33, Lo3, американским изолятом VA2, а также украинским изолятом UA1Gr. В исследуемом участке гена CP изолята SKS-18 выявлены уникальные аминокислотные замещения в положении 1 (Ser→Cys) и в положении 2 (Lys→Ala). Выводы. Изолят SKS-18 локализуется в одном кластере с изолятами с наибольшей идентичностью нуклеотидов, что может быть следствием их подобной изменчивости. Уникальные аминокислотные замещения в исследуемом участке гена CP изолята SKS-18 могут быть задействованы в семенной передаче вируса и других важных функциях инфекционного цикла, выяснение которых необходимо для разработки эффективных средств защиты растений от вирусных болезней.